Becker muscular dystrophy patient with a large intragenic dystrophin deletion: implications for functional minigenes and gene therapy. Issue 12 (December 1991) - Love, D R; Flint, T J; Genet, S A; Middleton-Price, H R; Davies, K E
Abstract : The genetic defects responsible for the allelic disorders of BMD and the more severe DMD have been shown to be mutations within the dystrophin gene, which encodes a 14 kb transcript. We describe here a BMD patient who belongs to a small class of subjects with large in frame deletions of the dystrophin gene that remove apparently dispensable coding sequence, thereby producing functional truncated dystrophin. The in vitro reconstruction of these deletion derivatives of full length dystrophin transcripts should enable higher efficiency transfection of human muscle or murine germline cells using retroviral based vectors, compared with the full length transcript. This capability offers a means of examining retroviral mediated transfer as a potential therapeutic strategy in severely affected DMD patients.